Oilbirds disperse large seeds at longer distance than extinct megafauna - Stevenson, Pablo R. (Sci Rep, 2021)
The extinction of megafauna in the Neotropics is thought to have reduced the potential of large seeds to be dispersed over long distances by endozoochory (ingestion by animals), but some seed dispersal systems have not been considered. We describe the role of oilbirds (Steatornis caripensis) as seed dispersers, in terms of seed width and dispersal distance (using GPS tracking devices), and we compare with data reported for other animals. Oilbirds dispersed seeds up to 29 mm wide, with a mean dispersal distance of 10.1 km (range 0–47.6 km). Some components of seed dispersal by oilbirds are outliers compared to that of other frugivores, such as the relationship between maximum seed width and body weight (however, few other extant specialized frugivores are also outliers). Estimates of mean dispersal distance by oilbirds are the largest reported, and we confirm that some living frugivores currently fulfil roles of seed dispersers and ecosystem services previously assumed to be only performed by extinct species.